Implementation of Meaningful Instruction Design Model Assisted by Comic on Students Understanding of Multiplication - Kusumawati, Indria; Firdaus, Fery Muhammad; Oktari, Viscal (UNNES JOURNAL, 2024)
The meaningfulness of math learning in multiplication material is still lacking. This can be seen from students who do not care when they get low results in multiplication learning and are considered boring for students. In overcoming these problems, it is necessary to have the meaningfulness of mathematics learning, one of which is through the Meaningful Instruction Design model with the help of Comics in achieving a better understanding of the concept of multiplication. The type of research used is pre-experiment with pretest-posttest one group de-sign design. The study population was 25 third grade students selected by random sampling technique with a sample of 20 students. From the results of hypothesis testing, the significance of 0.00 < 5% was obtained so that it was stated that the Meaningful Instruction Design model assisted by Comics had an effect on understanding multiplication. Based on the results of the study, students' understanding of multiplication can increase due to the implementation of the Meaningful Instruction Design model assisted by Comic media. However, in order to produce new contributions using the Meaningful Instruction De-sign model can be applied to other mathematics materials. Kebermaknaan pembelajaran matematika pada materi perkalian masih kurang. Hal ini dilihat dari siswa yang tidak peduli ketika mendapatkan hasil yang rendah pada pembelajaran perkalian serta dianggap membosankan bagi siswa. Dalam mengatasi masalah tersebut, perlu adanya kebermaknaan pembelajaran matematika, salah satunya melalui model Meaningful Instruction Design dengan berbantuan Komik dalam mencapai pemahaman konsep perkalian menjadi lebih baik. Jenis penelitian yang digunakan adalah pre-eksperimen dengan desain pretest-posttest one group design. Populasi penelitian sebanyak 25 siswa kelas III yang dipilih dengan teknik random sampling dengan sampel sebanyak 20 siswa. Dari hasil uji hipotesis diperoleh signifikansi 0,00 < 5% sehingga dinyatakan bahwa model Meaningful Instruction Design berbantuan Komik berpengaruh terhadap pemahaman perkalian. Berlandaskan hasil penelitian, pemahaman perkalian siswa dapat meningkat dikarenakan adanya implementasi model Meaningful Instruction Design berbantuan media Komik. Namun, agar dapat menghasilkan kontribusi baru menggunakan model Meaningful Instruction Design dapat diterapkan pada materi matematika lainnya.